The influence of employee benefits towards organizational commitment - Ju, Soon Yew; Kong, Lai Kuan; Hussin, Zaliha; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2008)
Employee benefits which included mandatory benefits and fringe benefits are becoming essential portion of the compensation packages that are offered by organizations to their employees. The purpose of this study was to reveal whether employee benefits offered by the organization are important as antecedents to organizational commitment for employees in food-manufacturing industry in the state of Kedah, Malaysia. A total of 161 employees responded to the survey. The results of the study suggested that mandatory benefits and fringe benefits were positively influenced organizational commitment. The results further denoted that fringe benefits fully mediated mandatory benefits when predicting organizational commitment. The implications of the findings were discussed.